(untitled) (Journal of Education and Development, 2021)
As colleges and universities around the world grapple with the continuing impact of the ongoing COVID-19 pandemic, it is necessary for research to not only focus on student academic learning issues, but also test for maintained support of needed student resources such as Academic Advising and Professional Development Centers. Using the Senior Student Satisfaction Survey, two separate samples of graduating business undergraduates at a Mid-Atlantic University in the United States of America were surveyed, in late Spring 2019 (pre-pandemic) and late Spring 2020 (early pandemic). The goals of this study were two-fold. The first was to test for changes from pre-pandemic to early pandemic in seven student-related perception measures: attendance motivation, coursework challenge, professional development engagement, academic advising ease/quality, professional development ease/quality, business degree satisfaction, and perceived market value to potential employers. The second goal was to test for changes in the perceived relationships of five “independent variables”, i.e., attendance motivation, coursework challenge, professional development engagement, academic advising center ease/quality, and professional development center ease/quality, to two “dependent variables”, i.e., business degree satisfaction and perceived market value to potential employers. Comparing pre-pandemic (2019) to early pandemic (2020) perceptual change data, this study found that both the Academic Advising and Professional Development Centers handled these student-based perception variables from the surveys quite well. When the campus was suddenly closed due to the pandemic, both Centers successfully made quick adaptive changes to virtual models to handle initial student needs.